2017
DOI: 10.1175/jamc-d-16-0291.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Turbulence Indicators Obtained from In Situ Flight Data

Abstract: Two indicators of turbulence—the eddy dissipation rate (EDR) and derived equivalent vertical gust velocity (DEVG)—are calculated using aircraft observations from Hong Kong–based airlines, whose aircraft included Boeing and Airbus models, for 39 months from February 2011 to April 2014. Characteristics of the two turbulence indicators that were calculated at 1-min intervals from the flight data are investigated. For Boeing and Airbus aircraft, there are large seasonal variations in the 90th and 99th percentiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 29 publications
1
34
1
Order By: Relevance
“…The primary peak falls within relatively small DEVG values (less than 8 m s -1 ), and the secondary peak falls within relatively large DEVG values (greater than 8 m s -1 ). This bimodal distribution, 25 which is more prominent in the NH (blue curve) than in the SH (red curve), is highly suspicious considering that Kim et al (2017) showed that the PDFs of the DEVG have a unimodal distribution following a lognormal distribution.…”
Section: Devg Datamentioning
confidence: 99%
See 3 more Smart Citations
“…The primary peak falls within relatively small DEVG values (less than 8 m s -1 ), and the secondary peak falls within relatively large DEVG values (greater than 8 m s -1 ). This bimodal distribution, 25 which is more prominent in the NH (blue curve) than in the SH (red curve), is highly suspicious considering that Kim et al (2017) showed that the PDFs of the DEVG have a unimodal distribution following a lognormal distribution.…”
Section: Devg Datamentioning
confidence: 99%
“…Stickland (1998) conducted a direct comparison between a vertical acceleration-based EDR and DEVG time series of Qantas Airways Boeing 747 data over a 3-month period (from October to December 1997) and showed that the two turbulence metrics are roughly correlated; however, this study considered a limited data period and only one aircraft type. Kim et al (2017) compared the EDR from some aircraft of Hong Kong-based airline (Haverdings and Chan, 2010) and the DEVG from the same aircraft using a relatively long period (39 months from February 2011 to April 2014) data. Kim et al (2017) developed 20 the best-fit curves between the EDR and DEVG for Airbus and Boeing aircraft data, separately.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The DEVG (Tenenbaum 1991;Gill 2014Gill , 2016Kim et al 2017) is calculated following Truscott (2000) using:…”
Section: Forecast Verificationmentioning
confidence: 99%